Fatwa & sains perubatan moden menurut perspektif Maqasid Syariah = Fatwa & modern medical sciences from the perspective of Maqasid Syariah - Rosman, Arieff Salleh; Ahmad Fadzillah, Nurrulhidayah; Haron, Zulkiflee; Ripin, Mohd Nasir; Hehsan, Aminuddin; Jandra, Mifedwil; Omar Jamli, Nor Azwa (UTM Press, 2019)
Modern medical science and technology innovates various treatment methods that require legal clarification in accordance with Islamic law. Fatwa institutions play a role in producing explanations and solutions that coincide with the objective of Islamic law (maqasid Syariah). Life preservation as one of the objective of Islamic law has a close relationship with medical science. The objective of this article is to analyze the relation of medical science with the the objective of Islamic law and to analyze the application of the objective of Islamic law in the modern fatwa related to medical sciences. This is a qualitative study using content analysis method. The findings show that medical science has a significant relationship with the achievement of the objective of Islamic law. Medical science based on Islamic law can fulfill the five basic needs that are the core of the objective of Islamic law. Medical science that cares for the health of individuals and societies help individuals and communities perform the perfect worship as well as the commitment of religious life with which it can safeguard muslim belief system. Medical science also safeguarding the safety of human life. Human intellect can only be maintained by practicing a healthy living culture. A healthy individual can build a healthy family and society to ensure the survival of human beings with which it can preserve the human descendants. Healthy community members can live productively to preserve their wealth.